Assessing Market (Dis)Integration in Early Modern China and Europe - Daniel M. Bernhofen; Markus Eberhardt; Jianan Li; Stephen Morgan (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper challenges established claims of comparable degrees of market integration in Europe and China on the eve of industrialization. Our empirical strategy focuses on the dynamics of price convergence and accounts for general equilibrium effects arising from common shocks and network effects. Using monthly grain prices for 1740-1820 our analysis uncovers a secular process of market disintegration in 221 prefectures of Qing China. Comparing our results with those for grain price panels from Western Europe we conclude that in terms of market integration the Great Divergence was well under way decades before the start of the 19th century.
Keywords: F15; N75; L11; C23; O10; 330; comparison of Chinese and western European market integration; price convergence; common factor model; cross-section dependence